Temporal and cross-sectional associations of serum per- and polyfluoroalkyl substances (PFAS) and lipids from 1986 to 2016 − The Tromsø study - Ana Carolina M F Coêlho; Dolley Charles; Therese Haugdahl Nøst; Lara Cioni; Sandra Huber; Dorte Herzke; Charlotta Rylander; Vivian Berg; Torkjel M Sandanger (Environment International)
Introduction: Per- and polyfluoroalkyl substances (PFAS) have been linked to effects on human lipid profiles, with several epidemiological studies reporting associations between specific PFAS and blood lipid concentrations. However, these associations have been inconsistent, and most studies have focused on cross-sectional analyses with limited repeated measurements. Objective: In this study, we investigated associations between serum PFAS concentrations and major blood lipid classes over a 30-year period (1986–2016) and up to five time points. Lipids analyzed included total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG). Methods: This study included 145 participants from The Tromsø Study, Norway, who donated plasma samples three to five times over the study period. Linear mixed-effects (LME) models assessed longitudinal associations between PFAS and lipid classes, while multiple linear regression (MLR) models were used for cross-sectional associations. Results: LME models demonstrated positive longitudinal associations between perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnDA), perfluorododecanoic acid (PFDoDA), and perfluorotridecanoic acid (PFTrDA) with TC. Additionally, PFOA, PFDA, PFUnDA, PFDoDA, and PFTrDA were associated with LDL-C, and PFUnDA and summed perfluorooctane sulfonate isomers (∑PFOS) with HDL-C. Cross-sectional analyses corroborated positive associations between the six PFAS compounds and TC at least three times, but the LDL-C and HDL-C associations were not confirmed. Summed perfluorooctane sulfonamide isomers (∑PFOSA) showed a negative association with LDL-C longitudinally, but this was not confirmed cross-sectionally. No associations were observed between PFAS and TG, longitudinally or cross-sectionally. Conclusion: Concentrations of multiple PFAS were positively associated with blood lipids in longitudinal analyses, with the most consistent associations observed between six PFCA compounds and TC. These findings highlight the need for further investigation into these complex associations.